Isolation of a simian virus 40 T-antigen-positive, transformation-resistant cell line by indirect selection. - Ryan, K W (1985)
In an attempt to identify cellular genes that might be involved in simian virus 40 (SV40) transformation, we have set out to isolate cells which express T antigen but are not transformed. SV40 DNA and the herpes simplex virus thymidine kinase gene were cotransfected into tk- 3T3 fibroblasts. Of 72 colonies screened that were resistant to hypoxanthine-aminopterin-thymidine, 57 were T antigen positive as judged by immunofluorescence. One of these lines, A27, had a normal growth phenotype in monolayer overgrowth and soft agar assays. It contained intact SV40 sequences that could be rescued by fusion to permissive cells. This rescued virus was fully capable of transforming nonpermissive cells to the same extent as did wild-type virus. The A27 cells, however, were not transformable by infection with SV40 or by transfection of SV40 DNA. It is likely that these cells were altered in a cellular function required for the establishment of the transformed state.